7.8k views
0 votes
Given the following information:

g(t) = 3t2 – 5t + 6
p(t) = 772-8t? - 9
Determine g(t) + p(t) in standard form.

PLEASE HELP!!!!!!!!​

Given the following information: g(t) = 3t2 – 5t + 6 p(t) = 772-8t? - 9 Determine-example-1
User KSigWyatt
by
5.5k points

1 Answer

5 votes

Answer:


2t {}^(2) - 5t - 3

Explanation:

You add the like-terms so the things that are the same, pretty much.

so 3t^2+7t^2 = 10t^2

and you can subtract 8t^2 from 10t^2 because they are like terms so you get 2t^2

then bring -5t down and subtract 9 from 6 and boom you're done

User RxRead
by
5.9k points